2023
DOI: 10.1155/2023/9471520
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of m7G-Related Genes and Chronic Hepatitis B: Diagnostic Markers, Immune Microenvironment Regulation, Disease Progression

Abstract: Chronic hepatitis B (CHB) is a major public health problem in the world. It is the main cause of liver cirrhosis and liver cancer. Although many important roles of RNA modification in stem cells or tumor diseases have been identified, the role of N7-methylguanosine (m7G) modification in the process of chronic HBV infection has not been clearly defined. Therefore, we conducted a systematic analysis on the process of chronic HBV infection. We found that a total of 18 m7G-related genes were altered in chronic HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…While the regulatory mechanisms of METTL1 and WDR4 by HBV have yet to be elucidated, our study provides evidence of HBV-mediated upregulation of METTL1 and WDR4 expression. This finding aligns with a report of increased expression of METTL1 and WDR4 in HBV-infected tissues, which is the only study investigating m7G modification in chronic HBV infection [32]. In that study, the investigators clarified the relationship between m7G-related genes in HBV-infected liver tissues and the immune microenvironment as well as disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…While the regulatory mechanisms of METTL1 and WDR4 by HBV have yet to be elucidated, our study provides evidence of HBV-mediated upregulation of METTL1 and WDR4 expression. This finding aligns with a report of increased expression of METTL1 and WDR4 in HBV-infected tissues, which is the only study investigating m7G modification in chronic HBV infection [32]. In that study, the investigators clarified the relationship between m7G-related genes in HBV-infected liver tissues and the immune microenvironment as well as disease progression.…”
Section: Discussionsupporting
confidence: 88%
“… 38 , 39 Through data mining, Zhang et al found that M7G-related genes can not only be used as diagnostic markers for chronic hepatitis B, but also participate in the regulation of immune microenvironment and play an important role in the progression of chronic hepatitis B. 40 Therefore, multi-omics combined analysis has great development potential and application value.…”
Section: Introductionmentioning
confidence: 99%